The mediating effect of force and velocity changes on power output enhancement in bench press throw after submaximal isometric conditioning activity in trained males - Koźlenia, Dawid; Krzysztofik, Michał (Biology of Sport, 2025)
This study examined the mediating effect of force and velocity changes on power output enhancement after isometric submaximal conditioning activity (CA) in trained males. Males aged 19–25 years, with at least three years of continuous resistance training, were randomly assigned to experimental (EG; n = 14) and control (CG, n = 12) groups. The CA consisted of four three-second sets of isometric bench presses, using a load of 70% one-repetition maximum (1RM) with a 60-second rest interval. Bench press throw (BPT) was performed at 30% 1RM at baseline (3 minutes before CA) and at 1, 4, 7, and 10 minutes after the CA. Set mean velocity (sMV), set mean force (sMF), and set mean power output (sMP) were analyzed. A repeated measures ANOVA revealed significant improvements in sMV ( F = 6.10; p < 0.01) and sMP ( F = 5.03; p < 0.01) with no significant differences in force values ( F = 0.47; p = 0.55). The enhancements in sMV and sMP were observed at 4 minutes after the CA compared to baseline ( p < 0.01) and were sustained during the subsequent minutes ( p < 0.05). Mediation analysis confirmed the observed improvements in power output were mediated by velocity enhancement (β = 0.37; p < 0.01) with an insignificant impact on force (β = -0.03; p = 0.61). Using a moderate submaximal load in hold isometric muscle action, the examined CA protocol effectively enhanced upper body power output through increased barbell velocity while showing no changes in force production.